Refractory cold agglutinin disease successfully treated with daratumumab. A case report and review of literature - Abdelaziz Mohamed (14777668) (2023)
Background Cold agglutinin disease (CAD) is immune-mediated hemolytic anemia. The disease is caused by cold reactive autoantibodies that induce hemolysis through the activation of the complement pathway. Most patients with CAD are elderly, and half may have refractory CAD that may not respond to the first-line treatment option (i.e. rituximab). Some cases are refractory to multiple lines of therapy, including chemotherapeutic agents, which might be toxic, especially for elderly patients. Daratumumab is a human monoclonal antibody targeting CD 38 glycoprotein, a transmembrane protein highly expressed in lymphoid and plasma cells. Daratumumab is currently approved for treating multiple myeloma and is used mainly as a combination therapy with other agents. Case presentation Our patient is a 69-year-old female diagnosed with CAD after presenting with severe anemia and significant circulatory symptoms. Rituximab was not effective in controlling her disease, and she refused other available chemotherapeutic agents due to their side effects profile. We used daratumumab combined with erythropoietin, which led to a dramatic response measured by stabilizing her hemoglobin levels and transfusion independence. Conclusion Our case is the third reported case of refractory CAD successfully treated with daratumumab, which suggests that daratumumab might be a potential agent for the treatment and control of refractory Cold Agglutinin Disease. Other Information Published in: Hematology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/16078454.2023.2252651